Equivalent Circuit Modelling of an L-shaped Patch Antenna by Optimizing the Lumped Elements Using Differential Evolution Algorithm - Toktas, Abdurrahim (International Journal of Intelligent Systems and Applications in Engineering, 2017)
L-shaped patch antenna (LPA) is formed by combining two monopole patch radiators. Proper modelling of a LPA using lumped elements is crucial in antenna design and analysis. In this study, a novel equivalent circuit (EC) modeling of an LPA using differential evolution (DE) optimization algorithm is presented. Two parallel branches each represents the monopole patch radiator compose the EC topology. In each branch, a serial resistance and inductance pair stands for patch conductor, a parallel resistance and capacitance pair symbolizes the dielectric substrate. The expressions of these eight lumped elements enclosing the antennaâs physical and electrical parameters accompanying with optimization variables are constituted considering the element definitions of microstrip transmission line (MTL). Return loss equation is derived through input impedance equation of the EC model. The variables are then optimally found by fitting the calculated return loss to the simulated results by DE algorithm. The proposed EC model is then verified through results of simulated and measured LPA. Moreover, real and imaginary parts of the EC input impedance are comparatively calculated. These show that the proposed EC model gives almost the same results in terms of important antenna parameters.